Virulence gene profile, antimicrobial resistance and multi-locus sequence typing of Salmonella enterica subsp. enterica serovar Enteritidis from chickens and chicken products - Zakaria, Zunita; Hassan, Latiffah; Sharif, Zawiyah; Ahmad, Norazah; Mohd Ali, Rohaya; Amir Husin, Suraya; Mohamed Sohaimi, Norfitriah; Abu Bakar, Shafini; Garba, Bashiru (MDPI, 2022)
This study was undertaken to determine the virulence, antimicrobial resistance and molecular subtypes of Salmonella in the Central Region of Peninsular Malaysia. A total of 45 Salmonella Enteritidis were detected from live chicken (cloacal swab), and chicken products (fresh and ready-to-eat meat) samples upon cultural isolation and serotyping. Similarly, an antimicrobial susceptibility test based on the Kirby Bauer disk diffusion method as well as antimicrobial resistance AMR genes, virulence determinants and multilocus sequence typing (MLST) typing were conducted after the Whole Genome Sequencing and analysis of the isolates. The results indicate that sequence types ST1925 (63.7%), and ST11 (26.5%) were the predominant out of the seven sequence types identified (ST292, ST329, ST365, ST423 and ST2132). The phenotypic antimicrobial profile corresponds to the genotypic characterization in that the majority of the isolates that exhibited tetracycline, gentamycin and aminoglycoside resistance; they also possessed the tetC and blaTEM β-Lactam resistance genes. However, isolates from cloacal swabs showed the highest number of resistance genes compared to the chicken products (fresh and ready-to-eat meat) samples. Furthermore, most of the virulence genes were found to cluster in the Salmonella pathogenicity island (SPI). In this study, all the isolates were found to possess SPI-1, which codes for the type III secretion system, which functions as actin-binding proteins (SptP and SopE). The virulence plasmid (VP) genes (spvB, spvC) were present in all genotypes except ST365. The findings of this study, particularly with regard to the molecular subtypes and AMR profiles of the Salmonella Enteritidis serotype shows multidrug-resistance features as well as genetic characteristics indicative of high pathogenicity.